2016
DOI: 10.5223/pghn.2016.19.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Associations among the Degree of Nonalcoholic Fatty Liver Disease, Metabolic Syndrome, Degree of Obesity in Children, and Parental Obesity

Abstract: PurposeTo analyze the associations among the degrees of nonalcoholic fatty liver disease (NAFLD) by ultrasonography and metabolic syndrome, degrees of obesity in children, and degrees of parental obesity.MethodsA total of 198 children with obesity who visited a pediatric obesity clinic were prospectively enrolled in this study. The severity of NAFLD based on ultrasonography was classified into no, mild, moderate, or severe NAFLD group. The degree of obesity based on the percentage over standard weight for heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…We speculate that obesity stimulates the second hit because of fibrosis since leptin may be an important link between obesity and fibrosis. Oh, et al29 also showed that the degree of NAFLD correlated with the degree of obesity. Obesity was shown to be required for the development of liver fibrosis in a steatohepatitis model 30…”
Section: Discussionmentioning
confidence: 95%
“…We speculate that obesity stimulates the second hit because of fibrosis since leptin may be an important link between obesity and fibrosis. Oh, et al29 also showed that the degree of NAFLD correlated with the degree of obesity. Obesity was shown to be required for the development of liver fibrosis in a steatohepatitis model 30…”
Section: Discussionmentioning
confidence: 95%
“…However, ultrasonographic examination is widely used to screen NAFLD in epidemiological research as it is non-invasive, safe, widely available and portable, and the sensitivity and specificity for detecting hepatic steatosis is acceptable; Second, the assessment of NAFLD degree was conducted by ultrasound, which might induce subjectivity and inconsistency. Although ultrasound might not be the golden standard evaluator for NAFLD degree, liver ultrasonography is a noninvasive method which is most commonly used to evaluate the degree of steatosis for NAFLD in the practice [ 39 ]. To reduce the subjectivity and improve the consistency between the assessments of ultrasound physicians, all experienced physicians involved in our study were well-trained.…”
Section: Discussionmentioning
confidence: 99%
“…However, PC:PE ratios that are higher than normal have also been shown to be associated with NAFLD. We have previously observed increased hepatic PEMT activity and PC:PE molar ratio in diabetic rats (25). In addition, glycine N-methyltransferase-deficient mice display increased PC synthesis through the PEMT pathway and, consequently, have a dramatically increased hepatic PC:PE molar ratio (26).…”
Section: Disparities In the Effects Of Pemt Deficiency In Different Mmentioning
confidence: 94%